2008
DOI: 10.2109/jcersj2.116.36
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of chitosan/brushite powders for bone cement composites

Abstract: Recently, calcium phosphate cements have been considered in medicine and dentistry because of their excellent biocompatibility and advantages in situ handling and shaping abilities. Nevertheless, low mechanical strength of these cements limits wider the clinical applications. The aim of this work was the synthesis of chitosan/brushite powders for preparing the calcium phosphate cements. The synthesis of brushite was carried out in the chitosan matrix from calcium chloride and sodium phosphate at moderate pH of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This indicated that the composite fibers formed a unique core-shell structure with shell of CaPO 4 and core of chitosan [ 425 ]. A similar formulation was prepared for further applications in self-setting biocomposites [ 426 ]. DCPA/BSA biocomposites were synthesized through the co-precipitation of BSA on the nanodimensional particles of DCPA performed in ethanol [ 427 ].…”
Section: Biocomposites and Hybrid Biomaterials Containing Capo mentioning
confidence: 99%
“…This indicated that the composite fibers formed a unique core-shell structure with shell of CaPO 4 and core of chitosan [ 425 ]. A similar formulation was prepared for further applications in self-setting biocomposites [ 426 ]. DCPA/BSA biocomposites were synthesized through the co-precipitation of BSA on the nanodimensional particles of DCPA performed in ethanol [ 427 ].…”
Section: Biocomposites and Hybrid Biomaterials Containing Capo mentioning
confidence: 99%
“…500 A similar formulation was prepared for further applications in bone cement biocomposites. 501 DCPA/BSA biocomposites were synthesized through the coprecipitation of BSA on the nanodimensional particles of DCPA performed in ethanol. 502 Nanodimensional DCPA was synthesized and incorporated into dental resins to form dental biocomposites.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Calcium phosphate materials have been increasingly employed in orthopedic and dental applications. Recently, much attention has been paid to calcium phosphate cements (CPCs) because of their advantages in comparison with calcium phosphate bioceramics, regarding in situ handling and shaping abilities [ 1 , 2 ]. The CPCs are obtained by an acid-base reaction in water between an acidic calcium phosphate and a basic calcium phosphate, giving an intermediate basicity calcium phosphate that precipitates [ 3 ].…”
Section: Introductionmentioning
confidence: 99%